Traditional knowledge, attitude and behaviour of indigenous people towards endangered wildlife conservation in Kon Plong District, Vietnam - Nguyen Thi Thien, Huong; Bui, Manh Hung; Nienartowicz, Andrzej; Dong Thanh, Hai; Nguyen Quoc, Dung; A, Siu; Tran Huu, Vy; Smith, Lynn (Ecological Questions, 2024)
Indigenous knowledge, attitudes, and perceptions of local people are very important concepts for wildlife conservation. Endangered wildlife species that live in Kon Plong forests have been under pressure from the communities living around them, including wildlife hunting, trapping, capturing, illegal logging, and encroachment for residential and production land. This study aims to understand the knowledge, attitude, and behaviour of indigenous people towards endangered wildlife in order to protect these species. Some participatory rural appraisal tools were used to discuss the situation and collect information in nine villages of four communes in Kon Plong District from December 2019 to March 2020. The results showed that the levels of knowledge about endangered wildlife among indigenous people in communes were statistically different. People’s knowledge of the law influenced their behaviour. Gender had the greatest influence on the level of knowledge. Most indigenous people had a positive attitude and wanted to protect endangered animals. “Commune” and “culture” were the two factors affecting people’s attitudes. “Commune”, “culture”, and the level of understanding affected the hunting behaviour of people. Negative human impacts have seriously influenced endangered wildlife species. Therefore, it is necessary to develop a long-term conservation strategy and plan, including the establishment of Kon Plong Special-Use Forests, supporting livelihoods for local people, communicating, and raising awareness among local people, and increasing the participation of community organisations.